2002
DOI: 10.1248/jhs.48.331
|View full text |Cite
|
Sign up to set email alerts
|

Release of Bisphenol A from Food Can Lining upon Heating.

Abstract: Nine different food cans, packed with water, were heat-treated for 30 min at 80 or 100°C in order to elucidate the trends associated with the leaching of bisphenol A (BPA) from internal coatings. Low levels of BPA were detected in water from all unheated cans, rising to 0.06 to 32 ng/cm 2 after heating at 100°C. Reducing the heat-treatment temperature to 80°C was found to reduce the BPA concentration in the contained water by up to two-thirds. The cans that recorded the highest BPA concentrations in water afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Compared to cans filled with water, increased amounts of bisphenol A migrated from cans filled with 1-10% sodium chloride, 5-20% glucose, or vegetable oils and heated to 1211C. Takao et al (2002) reported increased leaching of bisphenol A from cans into water when the cans were heated to Z801C.…”
Section: Fcpsa (2005)mentioning
confidence: 99%
“…Compared to cans filled with water, increased amounts of bisphenol A migrated from cans filled with 1-10% sodium chloride, 5-20% glucose, or vegetable oils and heated to 1211C. Takao et al (2002) reported increased leaching of bisphenol A from cans into water when the cans were heated to Z801C.…”
Section: Fcpsa (2005)mentioning
confidence: 99%
“…According to the thermal degradation pathway of BPA polycarbonate and the environmental fate of BPA, 4-CP, BPA, and phenols were the most suspected residues in canned foods [27][28][29][30]. Therefore, the specificity of the antibody and of the ELISA was determined by the crossreactivity studies with 11 structural analogues of BPA including the degradation products: PP, 4-CP, diOH-BP, hexestrol, DES, BPF, BPS, 4,4′-thiodiphenol, BPA-butyrate, BPA-valerate, and 4-hydroxybenzoic acid ( Table 2).…”
Section: Assay Specificitymentioning
confidence: 99%
“…Heat catapults the dissolution of DPA in the packed food in BPA coated food containers. 27 Preservation of canned foods by heating at 100 o C leads to an increased concentration of BPA estimated to be 1.7-55.4 times the normal concentration.…”
Section: Leaching Of Bpa From Food Cans and Containersmentioning
confidence: 99%